Ambient Functions: Abandoned Children to Zoos - Hurley, Chris (Archivaria, 1995)
Since records are timebound and contextual metadata must be understood by an observer whose frame of reference is different from that of the record-keeper, there is a need for external validation. The processes of terminological control (based on definition) are inadequate for this purpose. What is needed is a process of contextual control (based on observation). Ambience is the context of provenance and it is there that we will find external validation of provenance data. Functions offer one possible tool for crafting ambient relationships. Ambient functions define and give meaning to agents of record-keeping within the context in which they operate. Ambient functions should be distinguished from business activities and processes, which do not afford the basis for meaningful discrimination necessary when formulating appraisal categories and useful search patterns. RÉSUMÉ Puisque les documents appartiennent à leur époque et que la méta-information contextuelle doit être comprise par un observateur dont le cadre de référence est différent de celui d'un gestionnaire de documents, il y a un besoin de validation. Les processus de contrôle terminologiques (fondés sur l'observation) sont inadéquats. Un processus de contrôle contextuel basé sur l'observation est nécessaire. "L'ambiance" est le contexte de provenance et c'est là que l'on retrouvera la validation externe de l'information sur la provenance. Les fonctions constituent un outil possible pour constituer ces relations d'ambiance. Les fonctions ambiantes définissent et donnent un sens aux gestionnaires de documents à l'intérieur du contexte dans lequel ils oeuvrent. Les fonctions ambiantes doivent être distinguées des activités courantes et des différents processus qui ne requièrent pas un tri élaboré que nécessite la catégorisation des critères d'évaluation ou des plans de recherche.